Putting them on a strong spiritual path: Indigenous doulas responding to the needs of Indigenous mothers and communities - Jaime Cidro; Caroline Doenmez; Stephanie Sinclair; Alexandra Nychuk; Larissa Wodtke; Ashley Hayward (BMC, 2021)
Abstract Objective In the past few years, increasing numbers of Indigenous doula collectives have been forming across Canada. Indigenous doulas provide continuous, culturally appropriate support to Indigenous women during pregnancy, birth, and the post-partum period. This support is critical to counter systemic medical racism and socioeconomic barriers that Indigenous families disproportionately face. This paper analyzes interviews with members of five Indigenous doula collectives to demonstrate their shared challenges, strategies, and missions. Methods Qualitative interviews were conducted with members of five Indigenous doula collectives across Canada in 2020. Interviews were transcribed and returned to participants for their approval. Approved transcripts were then coded by all members of the research team to ascertain the dominant themes emerging across the interviews. Results Two prominent themes emerged in the interviews. The first theme is "Indigenous doulas responding to community needs." Participants indicated that responding to community needs involves harm reduction and trauma-informed care, supporting cultural aspects of birthing and family, and helping clients navigate socioeconomic barriers. The second theme is "Indigenous doulas building connections with mothers." Participants' comments on providing care to mothers emphasize the importance of advocacy in healthcare systems, boosting their clients' confidence and skills, and being the "right" doula for their clients. These two inter-related themes stem from Indigenous doulas' efforts to counter dynamics in healthcare and social services that can be harmful to Indigenous families, while also integrating cultural teachings and practices. Conclusion This paper illustrates that Indigenous doula care responds to a wide range of issues that affect Indigenous women's experiences of pregnancy, birth, and the post-partum period. Through building strong, trusting, and non-judgemental connections with mothers and responding to community needs, Indigenous doulas play a critical role in countering medical racism in hospital settings and advancing the resurgence of Indigenous birthing sovereignty.